Complexities of adolescent learner behaviour within multicultural indigent societies - Mkuzo, Nkosivelile Nkosivile Nkosiyamntu (University of the Free State, 2020)
This study was prompted by school principals and teachers complaining about bullying, gangsterism, drug abuse and excessive masculinity, as demonstrated by initiates returning from traditional initiation schools. They reported that this situation was exacerbated by the abolition of corporal punishment, without alternative means of disciplining learners. Literature shows that in South Africa, as in other countries, negative learner behaviour takes the form of drug and alcohol abuse, bullying and disrespect from the side of traditional initiates, to mention a few examples. I identified gaps related to multiculturalism and learner behaviour, the linking of adolescent learner behaviour to poverty, and the lack of understanding of the legal framework for learner discipline. The main aim of the study was to critically examine the complexities of adolescent learner behaviour within multicultural indigent societies. The study was done in the poverty-stricken area of the Joe Gqabi District within the Elundini Local Municipality in the Eastern Cape. Participants from six schools from the townships, rural areas and semi-urban areas took part in the study. Interviews targeted principals, LRCs, SGBs, TLO, LO teachers, government officials and community members. The research and paradigm approaches used in this study were the qualitative approach and interpretivism, respectively. The study was premised on three theories: Social Discipline Model, Psychosocial Development Theory, and Theory of Lower Class Culture. Common among the theories is that they all stress the negative influence of identity, culture, and the need for belonging on learner behaviour. The integrity of the study was ensured by paying attention to ethical issues, and the question of credibility, consistency and transferability. The findings of this study include that the complexities of adolescent learner behaviour take the form of a complex inter-connection of forms of behaviour. For instance, gangsterism was found to be connected to bullying, disrespect for teachers, learner-on-learner violence, reckless sexual behaviour, substance abuse, defiance from young men returning from the initiation school, machismo, occult beliefs and learners misbehaving to please their peers in order to believe themselves belonging and being acceptable. Issues that contribute to the complexities of adolescent learner behavior can be classified as teacher-related, home/parent related, those related to culture, and social relations and peer group influence emanating from the need for identity. Socio-economic conditions is a unique factor impacting on the complexities of adolescent learner behaviour in the context of indigent societies. A serious disjuncture exists between the intended values of the initiation school and the actual values learned at the initiation school, on the one hand, and the values of the formal schooling system, on the other. Based on the findings and theories, I recommend a multidimensional approach that includes many categories of stakeholders. I also recommend a model based on democratic principles entitled Equal Partnership for Winning Co-operation: Shared Responsibility in a Democratic Setting. In conclusion, all stakeholders need to be involved in crafting policies that regulate learner behaviour. This study revealed the powerful influence of culture on adolescent learner behaviour. Poverty renders adolescent learners, and girl learners in particular, vulnerable in their need to support themselves and their families. In extreme cases parents even approve of some of the complexities of adolescent learner behaviour, such as cross-generational affairs of girls with older men for the sake of material gain. Some parents even allow the marriage of their daughters by abduction. It is my sincere wish that fighting poverty should not just be used as cliché or as a tool for electioneering by politicians. A concerted effort should be exerted to save these learners’ futures from poverty.
Thesis (Ph.D. (Education Studies))--University of the Free State, 2020
Keywords: Defiant; Identity; Belonging; Poverty; Acceptance; Occult; Multiculturalism -- study and teaching; Indigenous peoples -- study and teaching